The Relationship Between Intrinsic And Extrinsic Motivation And Athletic Participation In Students - Sutriawan, Agus agus; Hakim, Hikmad; Ilyas, Muslim Bin (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2025)
This study aims to analyze the relationship between intrinsic motivation and extrinsic motivation with athletic participation among students of MAN Insan Cendekia Gowa. The research employs a quantitative approach using a correlational method. The study population consists of students actively engaged in athletic activities, with a sample size of 35 students selected through purposive sampling. The research instruments include questionnaires to measure intrinsic and extrinsic motivation as well as athletic participation. Data were analyzed using Pearson's correlation test to determine the relationships between the variables studied. The results show a significant relationship between intrinsic motivation and athletic participation (N = 35, r = 0.297, p = 0.003) and between extrinsic motivation and athletic participation (N = 35, r = 0.307, p = 0.000). Based on these findings, it can be concluded that both intrinsic and extrinsic motivation significantly contribute to the level of students' athletic participation. This study provides important implications for educational administrators and sports coaches to consider motivational aspects in enhancing students' athletic participation.